WACANA PEMBANGUNAN MELALUIPENGGALIAN NILAIBUDAYA - T. Sihol Nababan (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2004)
The study of culture-development value, i.e. "the study of worldview-work ethos " should find the culture values including work ethos and worldview that applied and have the process of mentality and intellegence creation to increase the quality of life, to find how the culture values can be reinterpreted so that have the functional value to gain the prosperity. Besides, it is also hoped to find the individual and society group as the target of programs of culture value interpretation, so that the changes become effective and efficient. The study is the continuation study that succeed in finding the existence of difference between economic and society development, and also the linkage of culture value based on religious values and work ethos.